Design of a medical‐grade QoS metric for wireless environments. Issue 8 (24th March 2014) - Park, Kyung‐Joon; Lee, Hyung‐Ho; Choi, Sunghyun; Kang, Kyungtae
Abstract: In this letter, we introduce medical‐grade quality of service (QoS) for wireless healthcare applications. We first investigate the basic QoS requirements of medical applications. We point out that the conventional QoS metric of the packet error rate (PER) is insufficient for evaluating the QoS level of medical applications. The most critical concern in medical‐grade QoS is whether the received data can be diagnosed by medical personnel, that is, medical diagnosability . As a prevailing application, we present a medical‐grade QoS metric for wireless electrocardiogram (ECG) transmission. The introduced QoS metric, called weighted diagnostic distortion (WDD), can properly evaluate medical‐grade QoS by reflecting the main diagnostic features of an ECG signal. Our simulation results demonstrate that there can be a significant discrepancy between WDD and PER, which confirms the importance of developing a medical‐grade QoS metric by properly taking into account the key characteristics of medical traffic. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this letter, we introduce medical‐grade quality of service (QoS) for wireless healthcare applications. As a prevailing application, we present a medical‐grade QoS metric for wireless electrocardiogram(ECG) transmission. The introduced QoS metric, called weighted diagnostic distortion, can properly evaluate medical‐grade QoS by reflecting the main diagnostic features of an ECG signal.